2018
DOI: 10.14233/ajchem.2018.21436
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions and Refractive Indices: Experimental Data and Prediction of Oxygenated Fuel Additives with Hydrocarbons

Abstract: Oxygen containing compounds specifically alkanol and ether are being used as oxygenate fuel additives. The refractive indices (nD) of oxygenated fuel additive, aliphatic and aromatic hydrocarbon and their mixtures were measured at 298.15 K to 318.15 K. The mixtures selected were diisopropyl ether (DIPE) + benzene, toluene, n-alkane (C6-C8) or benzene, toluene (1) + alkane (2) and all possible combinations of alkanes at 298.15 K to 318.15 K. Various mixing rules like Gladstone-Dale, Arago-Biot, Heller, Weiner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study of thermophysical properties is of considerable importance to test the existing models, theories, and correlations and to understand intermolecular interactions in chemical designing. The physicochemical properties of compounds in multicomponent fluid mixtures are important for designing distillation columns for separation process refineries. The measurement of these properties for multicomponent mixtures beyond binaries is time-consuming, costly, and difficult also due to the plethora of compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of thermophysical properties is of considerable importance to test the existing models, theories, and correlations and to understand intermolecular interactions in chemical designing. The physicochemical properties of compounds in multicomponent fluid mixtures are important for designing distillation columns for separation process refineries. The measurement of these properties for multicomponent mixtures beyond binaries is time-consuming, costly, and difficult also due to the plethora of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Excess properties were studied for the binary mixtures of benzene + n -heptane and benzene + n -octane. ,, But through a literature survey, we confirmed that there is no experimental study for the ternary benzene + n -heptane + n -octane system. This paper is a part of study on the thermophysical properties of oxygenated fuel mixtures consisting of diisopropylether, ethanol, benzene, and alkane (C 6 –C 9 ). , Benzene is an important constituent of gasoline due to its high octane number, and n -heptane and n -octane are also the hydrocarbons present in gasoline. Therefore, this paper report the density (ρ), excess molar volume ( V m E ), speed of sound ( u ), and refractive index ( n D ) of ternary mixtures containing benzene, n -heptane, and n -octane at temperatures of 298.15, 308.15, and 318.15 K and a pressure of 0.1 MPa.…”
Section: Introductionmentioning
confidence: 99%